(untitled) (Libyan Journal of Ecological & Environmental Sciences and Technology, 2020)
This study aimed to determine some physical and chemical properties of some olive oil, collected from the local market in Libya. Samples were collected from Awinya- Aljabal Algharbi, Brack Alshati, Sebha, and Ubari. There were no significant differences in physical properties of all examined samples. However, the chemical properties were as following; acidity was between (0.5890±0.024-%16.552±0.232). The lowest value of peroxide was recorded in Awinya sample 5.50±0.231 mEq O2/Kg, and the highest value was in stored olive oil sample 54.00±0.213 mEq O2/Kg. Iodine value was between (65.50±0.132 in stored sample and 93.65±0.007 in Brack sample). Saponification values were between (188.50±0.111 and 252.55±0.152) Generally the results of chemicals analysis were within Libyan standards.